microRNA miR-14 acts to modulate a positive autoregulatory loop controlling steroid hormone signaling in Drosophila. - Varghese, J.; Cohen, S.M. (Genes & Development, 2007)
The insect steroid hormone Ecdysone and its receptor play important roles during development and metamorphosis and regulate adult physiology and life span. Ecdysone signaling, via the Ecdysone receptor (EcR), has been proposed to act in a positive autoregulatory loop to increase EcR levels and sensitize the animal to ecdysone pulses. Here we present evidence that this involves EcR-dependent transcription of the EcR gene, and that the microRNA miR-14 modulates this loop by limiting expression of its target EcR. Ecdysone signaling, via EcR, down-regulates miR-14. This alleviates miR-14-mediated repression of EcR and amplifies the response. Failure to limit EcR levels is responsible for the many of the defects observed in miR-14 mutants. miR-14 plays a key role in modulating the positive autoregulatory loop by which Ecdysone sensitizes its own signaling pathway.